2020
DOI: 10.1016/j.pedneo.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium glycerophosphate in neonatal parenteral nutrition solutions to increase calcium and phosphate compatibility for preterm infants

Abstract: Background: Preterm infants require higher calcium and phosphate intake than term infants to facilitate adequate bone growth, but this is rarely met in parenteral nutrition (PN) solution because of the limited solubility of calcium and phosphate. This study aimed to evaluate the solubility of organic phosphate with calcium gluconate in neonatal PN solutions, simulating its clinical use. Methods: PN solutions were composed of calcium gluconate at 50 mEq/L and sodium glycerophosphate (NaGP) at 25 mmol/L. Another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, the role of phosphates (inorganic or organic) on the stability of PN admixture and therefore their impact on compatibility cannot be ignored. It is well known that PN formulations containing the organic source of phosphates are less prone to destabilization [ 35 , 36 ]. Therefore, drugs compatible with PN admixtures based on organic phosphates cannot be expected to behave in the same way when the phosphate source in PN admixtures is changed to inorganic.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of phosphates (inorganic or organic) on the stability of PN admixture and therefore their impact on compatibility cannot be ignored. It is well known that PN formulations containing the organic source of phosphates are less prone to destabilization [ 35 , 36 ]. Therefore, drugs compatible with PN admixtures based on organic phosphates cannot be expected to behave in the same way when the phosphate source in PN admixtures is changed to inorganic.…”
Section: Resultsmentioning
confidence: 99%
“…In part, this is due to concerns about stability of these substances in solution and the possibility of precipitation. Studies continue in this area, especially as there is a pressing need to optimise calcium and phosphate delivery to prevent metabolic bone disease of prematurity 40…”
Section: Barriers To Achieving Nutritional Targetsmentioning
confidence: 99%
“…Therefore, the calcium and phosphorous should be in the most soluble form possible. Newer solutes in TPN, such as the use of use of sodium glycerophosphate can help decrease calcium and phosphorous precipitation in the solution thereby increasing the amount the infant receives per bag of TPN [23 ▪ ].…”
Section: Treatmentmentioning
confidence: 99%
“…Michaud et al evaluated the risk for future fractures in preterm infants and found that preterm birth was mainly associated with fractures before 18 months of age [18–20]. Other studies suggest that infants with MBDP are 16 times more likely to have rib and long bone fractures before 6 months than infants with no MBDP [23 ▪ ].…”
Section: Postneonatal Icu Management and Considerations For The Prima...mentioning
confidence: 99%